2014
DOI: 10.1007/s12134-014-0368-y
|View full text |Cite
|
Sign up to set email alerts
|

International Medical Graduates (IMGs) in the UK—a Systematic Review of Their Acculturation and Adaptation

Abstract: International medical graduates (IMGs) constitute about 23-28 % of the medical workforce providing support and contribution to the UK, Canada, USA and Australia. This review will inform the need for trainers, deaneries and colleges to plan and develop strategies to enhance the potential of IMGs. The authors aim to review and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 53 publications
(74 reference statements)
1
26
0
Order By: Relevance
“…Systematic reviews on migration of HRH, in the literature, have focused on trends in workforce migration [ 57 ], but not compared the motives across health care professionals. Integration studies have focused on qualitative thematic analyses of lived experiences, particularly in relation to nurses [ 54 , 58 , 59 ] and on doctors [ 60 ], but none on dentists. This review is a starting point examining the drivers of migration and integration experiences of the three professions of nursing, medicine and dentistry, which are different in relation to the professional’s control of their work environment, their professional and social identities [ 17 , 20 , 27 , 28 , 36 , 38 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews on migration of HRH, in the literature, have focused on trends in workforce migration [ 57 ], but not compared the motives across health care professionals. Integration studies have focused on qualitative thematic analyses of lived experiences, particularly in relation to nurses [ 54 , 58 , 59 ] and on doctors [ 60 ], but none on dentists. This review is a starting point examining the drivers of migration and integration experiences of the three professions of nursing, medicine and dentistry, which are different in relation to the professional’s control of their work environment, their professional and social identities [ 17 , 20 , 27 , 28 , 36 , 38 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…These topics also emerged in this review but were—except for patient-centered care—described as differences of the home and the new culture and not as problems. In addition, difficulties for the foreign physicians with the concept of shared decision-making as described by Khan et al (2014) [ 10 ] were not found. The results of this review indicate that the IMGs did not consider this concept as problematic.…”
Section: Discussionmentioning
confidence: 99%
“…Given that differences in medical education and learning styles exist, particularly between western and other countries, 16 it is not surprising that IMG residents were noted to experience learning challenges within the Canadian context. Medical education in Canada is based on principles of adult self-directed learning, is problem-based, focuses on the development of critical thinking skills, and emphasizes collaboration and relative equality between teacher and learner.…”
Section: Discussionmentioning
confidence: 99%